'These mountains are unlike ours': my interactions with camp refugees in Greece. (4th May 2018) - George, Nabil George
Abstract: The recent regional crises affecting the Middle East and Mediterranean have seen masses of people move away from conflict and devastation to safer territories. A large movement has occurred to the European nations bordering these conflict zones. Greece, along with other countries, has become a focal point for refugees avoiding warfare and daily struggle from said regions, seeking asylum and safety. The dangerous journeys by land and sea are risks taken by many to escape atrocities and disaster. This case-report aims to highlight aspects of this migration from conflict zones through a simple conversation between the refugee community and aid relief workers. The focus of the paper is on the Yazidi community from Iraq, who were temporarily accommodated in campsites in Greece, having suffered horrendously. The events described by the refugee community are conveyed in English, as translated by the author from Arabic